Energy Substitution: When Model Selection Depends on the Focus - Behl, Peter; Dette, Holger; Frondel, Manuel; Tauchmann, Harald (Energy Economics, 2013)
In contrast to conventional model selection criteria, the Focused Information Criterion (FIC) allows for the purpose-specific choice of model specifications. This accommodates the idea that one kind of model might be highly appropriate for inferences on a particular focus parameter, but not for another. Ever since its development, the FIC has been increasingly applied in the realm of statistics, but this concept appears to be virtually unknown in the literature on energy and production economics. Using the classical example of the Translog cost function and production data for 35 U.S. industry sectors (1960–2005), this paper provides for an empirical illustration of the FIC and demonstrates its usefulness in selecting production models, thereby focusing on the ease of substitution between energy and capital versus energy and labo
WiSo-Import:2015-03-26:4657